International financial reporting standards (IFRS) and Indian accounting practices - Raiyani, Jagadish R.; Lodha, Gaurav (New Delhi, India : New Century Publications, 2012)
Economic reforms initiated in India since early 1990s have led to increasing attention being devoted to accounting standards as a means towards ensuring potent and transparent financial reporting by corporations. International Financial Reporting Standards (IFRSs) - issued by the International Accounting Standards Board (IASB) as the uniform language of business to protect the interests of international investors - have brought into focus the need for reforms in accounting procedures in different countries. IFRSs have been made applicable in India for specified business entities. The new accounting norms have posed challenges for business enterprises in terms of presentation of accounts, and accounting policies and procedures. This book explains the requirements of IFRSs and the attending implementation hurdles in India.
Includes bibliographical references and index.
Keywords: Accounting -- Standards -- India; International business enterprises -- Accounting -- Standards; Financial statements -- Standards -- India; Financial statements -- Standards